Integration of Teaching Games for Understanding in Physical Education Learning: Improving Students' Motor Competence through Volleyball Game Modification - Apriani, Leni; Bausad, Andi Anshari; Alpen, Joni; Amran, Zaiful; Setiawan, Budi Arif (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Motor competence is a crucial aspect of the development of elementary school-aged children. The Teaching Games for Understanding (TGfU) model is considered capable of improving motor skills through a contextual and participatory approach to play. However, empirical evidence in local contexts, particularly regarding the effectiveness of TGfU on locomotor and object control skills separately, as well as gender differences, remains limited. This study used a quantitative approach with a one-group pretest-posttest quasi-experimental design. A total of 54 fifth-grade students of SD Negeri 190 Pekanbaru participated in TGfU-based volleyball learning for 6 weeks (12 sessions). The Test of Gross Motor Development, Second Edition (TGMD-2) assessed locomotor and object control skills. Because the data were not normally distributed (Shapiro–Wilk p < 0.05), analysis was performed using the Wilcoxon test. Results showed that TGfU was associated with improvements in overall motor competence (W = 3.5; z = –6.06; p < .001; Median = 4.0, 95% CI [3.5, 4.5], Effect Size = .99), locomotor skills (V1: W = 14; z = –5.47; p < .001; Median = 3.0, 95% CI [2.5, 3.5], Effect Size = .97), and object control skills (V2: W = 16; z = –5.80; p < .001; Median = 2.5, 95% CI [2.0, 3.0], Effect Size = .97). Female students showed greater improvement in locomotor aspects than males. Further research, employing a randomized controlled design and long-term retention testing, is recommended to strengthen the generalizability of these findings.